Surveillance systems for capture fisheries - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
An introduction to monitoring, control and surveillance systems for capture fisheries prepared by P Flewwelling 1994 217pp ISBN 925 103584 9